Analisis SWOT dalam Merumuskan Strategi Kompetitif Pada Industri Otomotif - Anggraini, Tari; Indarwati, Tias Andarini (Seminar Nasional Manajemen, 2025)
Business competition in the automotive sector, particularly in the two-wheeler industry, has become increasingly intense along with the growing number of manufacturers and dealers offering similar products. Yamaha SIP Kedungdoro is one of Yamaha’s official dealers strategically located in Surabaya, providing sales services, maintenance, and genuine spare parts. In order to remain competitive, Yamaha SIP Kedungdoro must adopt appropriate marketing strategies by taking into account both internal and external environmental conditions. This study aims to identify the internal and external factors of Yamaha SIP Kedungdoro and to formulate suitable competitive strategies through a SWOT analysis. The research employed a descriptive method, with primary data collected through direct observation, documentation studies, and interviews. The findings indicate that, based on the SWOT analysis, the most appropriate strategy to enhance the competitiveness of Yamaha SIP Kedungdoro is an aggressive strategy, which involves leveraging its strengths to seize all available opportunities.